Management of Tuberculosis Infection: Current Situation, Recent Developments and Operational Challenges - Agbota, Gino; Bonnet, Maryline; Lienhardt, Christian (Pathogens (Basel), 2023)
Tuberculosis infection (TBI) is defined as a state of infection in which individuals host live Mycobacterium tuberculosis with or without clinical signs of active TB. It is now understood as a dynamic process covering a spectrum of responses to infection resulting from the interaction between the TB bacilli and the host immune system. The global burden of TBI is about one-quarter of the world’s population, representing a reservoir of approximately 2 billion people. On average, 5–10% of people who are infected will develop TB disease over the course of their lives, but this risk is enhanced in a series of conditions, such as co-infection with HIV. The End-TB strategy promotes the programmatic management of TBI as a crucial endeavor to achieving global targets to end the TB epidemic. The current development of new diagnostic tests capable of discriminating between simple TBI and active TB, combined with novel short-course preventive treatments, will help achieve this goal. In this paper, we present the current situation and recent developments of management of TBI and the operational challenges.